Biofuels as a challenge of sustainable development - Saša Papuga; Aleksandra Kolundžija; Milica Đurđević (Zaštita Materijala)
Bioenergy, or energy derived from biomass, today is recognized as an important component in many energy scenarios, being an integral part of various global, regional, and national policies and strategies. This has led to intensified research into more efficient biofuel production. This paper explains the advantages, disadvantages, and problems related to the production of biofuels from different types of raw materials. Several examples of commercialized and demonstration plants for the production of biofuels in different parts of the world are listed. It is to be expected that, with greater use of modern biofuel production solutions, the contribution of these sources of (bio)energy will be the main part of future energy consumption from renewable sources.